'My task is to get into the French army': Soviet strategy and the origins of Soviet-French military cooperation in the 1930s. Issue 5 (29th July 2021) - Vershinin, Aleksandr
ABSTRACT: This article is about the first attempts of Soviet-French rapprochement in the military sphere in the early 1930s. It is based largely upon unpublished documents from the Soviet foreign policy (AVPRF), military (RGVA) and the communist party (RGASPI) archives in Moscow. It contends that for the top leadership of the USSR the political rapprochement with France did not necessarily lead to making a fully-fledged military alliance. Despite the attitude of Soviet diplomats in Paris, Moscow remained distrustful of the French. It considered military cooperation with them as a way to reinforce the Red Army and strengthen international positions of the USSR without taking excessive obligations.